2021
DOI: 10.1007/s10068-021-00916-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antinutrients, phenolics, antioxidant activities and in vitro α-glucosidase inhibitory activity in pumpkin leaves (Cucurbita moschata) during different domestic cooking methods

Abstract: Pumpkin leaves (Cucurbita moschata) were subjected to different household cooking methods (boiling, microwaving, steaming, and stir-frying) to evaluate their effect on antinutrients, phenolic compounds, antioxidant properties (ABTS, and DPPH) and in vitro a-glucosidase activity. All cooking methods studied significantly reduced the antinutrients and antioxidant activities, whilst phenolic compounds p-coumaric and ferulic acids significantly increased. The cooking methods reduced the oxalates by more than 50%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…This could also be due to certain compounds concentrated in this fraction that may have higher antioxidant activities. The antioxidant activity of pumpkin leaves was reported to be correlated to the concentration of phenolic compounds [31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could also be due to certain compounds concentrated in this fraction that may have higher antioxidant activities. The antioxidant activity of pumpkin leaves was reported to be correlated to the concentration of phenolic compounds [31].…”
Section: Resultsmentioning
confidence: 99%
“…Trans-4-feruloylquinic acid separated the raw leaves from the cooked African pumpkin leaves. The basis for the ranking of metabolites was on their VIP scores, with only top-ranking metabolites with the highest VIP scores considered [31]. Among the top eight metabolites with VIP scores greater than 1 were trans-4-feruloylquinic acid, rhamnetin-3-O-glucoside, cis-4-feruloylquinic acid, trans-4-coumaroylquinic acid, β-D-glucosyl-2-coumarate (Melilotoside), quercetin 3-galactoside and pseudolaroside A (Figure 1E).…”
Section: Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These two methods estimate the free radical scavenging activities of antioxidants [ 45 ]. The IC 50 value is the concentration needed for 50% inhibition and determines the strength of the inhibitor [ 19 , 46 ]. The antioxidant activities of African pumpkin leaves cooked by adopting four different house hols cooking methods are given in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Following the destruction of the cell walls of the leaves by microwave and boiling, it is likely the antinutritive compounds leached out into the boiling water. After boiling pumpkin leaves, Mashitoa et al [ 46 ] reported reduced tannin concentrations (46.24%). Due to contact of the boiling water with the plant material, boiling has the highest leaching compared to the other cooking methods and thus leads to a higher reduction of tannins and alkaloids than other cooking methods [ 17 , 46 ].…”
Section: Resultsmentioning
confidence: 99%